Adhesion Properties of Styrene-Butadiene-Styrene Triblock Copolymer-Based Pressure-Sensitive Adhesives for Protecting Opto-functionalized Sheets - Choi, D.J.; Hong, Y.K.; Chung, K.H. (Asian Journal of Chemistry, 2013)
Various pressure sensitive adhesives based on the types of tackifier were designed and their physical properties were analyzed. The behaviour of pressure sensitive adhesives transfer on an opto-functionalized sheet was examined. Pressure sensitive adhesives was prepared by adding various tackifiers with different molecular weights and softening points to styrene-butadiene-styrene. The physical properties of pressure sensitive adhesives were analyzed by measuring the peel strength, initial tack, holding power and contact angle obtained after coating the pressure sensitive adhesives onto a polypropylene film. The changes in the physical properties of pressure sensitive adhesives after adding an additional curing agent were also observed at various UV exposure times. The peel strength and initial tack increased with decreasing softening point of tackifier. An increasing trend of pressure sensitive adhesives transfer was also observed with increasing peel strength. In the case where a curing agent was added to the adhesive showing pressure sensitive adhesives transfer, the peel strength and initial tack decreased with increasing UV exposure time and amounts of curing agent, whereas the holding power increased.